An approximate method for intact stability of fishing vessels - Yilmaz, H; Kükner, A (SOC NAVAL ARCH MARINE ENG, 1999)
is well known that stability is the most important safety requirement for ships. One should have some information on ship stability at the preliminary design stage in order to reduce risk. Initial stability of ships is an important criterion and can be closely evaluated in terms of form parameters and vertical center of gravity. In this study, using some sample ship data, approximate formulations are derived by means of regression analysis for the calculations expressed in terms of strip preliminary design parameters that can easily provide approximate GM calculations. Thus designers can be provided with ship stability at the preliminary design stage, and also a set of appropriate design parameters for improving vessel stability can easily be determined.
Keywords: Engineering; Oceanography